Aktifitas Antifungi Ekstrak Daun Sembung Rambat (Mikania micrantha Kunth.) Asal Cileungsi, Bogor terhadap Trichophyton mentagrophytes - Hamida, Fathin; Agustin, Anglia Ananda; Djuhariyah, Yayah Siti (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
American rope leaves (Mikania micrantha Kunth.) contains secondary metabolites such as flavonoids, tannins, saponins and steroids. This study aimed to observe antifungal activity of ethanol extract 96% of american rope leaves were 200 mg/mL, 400 mg/mL, and 600 mg/mL concentration against Trichophyton mentagrophytes by disc diffusion method on Sabouraud Dextrose Agar (SDA) medium. Ketoconazole were positive control. The results showed that the 96% ethanol extract of american rope leaves had antifungal activity against Trichophyton mentagrophytes. The minimum inhibitory concentration of 96% ethanol extract of american rope leaves against Trichophyton mentagrophytes at 100 mg/mL.